Efficacy of Innovated Four-Stroke Gasoline Engine Trainer: It's Technical Enhancement to Grade 12 Senior HS Students - Valdehueza, Jefford Vinson (JPAIR Multidisciplinary Research, 2019)
Constantly, engine before all ages until today has a piston in it. Reciprocating up and down movement of a piston that converted to rotary motion by crankshaft can never be changed. This study facilitated students in developing their understanding of the operation of four-stroke cycle fundamentals using simulated cut-away parts of an engine. The study used a descriptive research design. Descriptive statistics were used to describe the students' survey responses. Inferential statistics (one-tailed t-test) was used to establish the difference between post-test and pre-test results of the written examination, simulation and practical examination. The study was conducted to the 24 senior high automotive Grade-12 students of Lapasan National High School-Gusa Annex during the second semester of School Year 2017-2018. As a result, the study found a significant difference in the respondents' pre-test and post-test scores. It helps 100% of the respondents' to pass the national certification level-1. Generally, the students can easily perform simple to complicated tasks; they become self-reliant, confident in handling the actual operation of engine servicing given such advantages. A corollary to this, the said innovation considered and re-assessed toward sustained improvement the researcher should use the results of the study for deeper analysis of issues and concerns on four-stroke cylinder gasoline engine trainer and as a benchmark measure to increase students' academic performance.
Keywords: Automotive Piston Stroke; Instructional Material; Innovated trainer; Experimental research; descriptive design; Senior High School; Philippines